Observasi Penyakit pada Tanaman Kopi Arabika (Coffea arabika L.) di Perkebunan Kopi Solok Radjo - Waruwu, Arifda Ayu Swastini (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Arabica coffee (Coffea arabica L.) is one of the high economic value plantation commodities widely cultivated in the highland areas of West Sumatra. This study aimed to identify diseases affecting Arabica coffee in the Solok Radjo Cooperative plantation. The study was conducted in coffee plantation by the Solok Radjo Cooperative and Laboratory of the Agroecotechnology, Department of Plantation Crop Cultivation, Faculty of Agriculture, Andalas University, Dharmasraya, West Sumatera. Field surveys were carried out on plants exhibiting disease symptoms, followed by visual documentation, sampling of infected tissues, and laboratory analysis through microscopic observation and morphological identification of pathogens. The results revealed three major diseases: leaf rust (Hemileia vastatrix), leaf spot (Cercospora sp.), and fruit rot (Fusarium sp.), all of which have the potential to reduce coffee bean productivity and quality. These findings provide a scientific basis for developing effective and sustainable disease management strategies to support the improvement of Arabica coffee quality and production